Gain Competitive Advantage by Transcending the Front-Line Paradox - Pedersen, Carsten; Pedersen, Carsten (MIT Sloan Management Review, 2021)
Front-line employees can offer essential insights to be used in strategic decision-making, yet top management teams rarely ask these employees about strategic issues. In so doing, leaders are depriving themselves of new information that could improve their analyses, and they risk making decisions in isolation within the C-suite echo chamber. But the right tools and training can equip employees to better understand forecasting and teach executives to recognize their insights.